Islamic Economic Law Review: Application of Khiyar Rights to Brick Purchases: English - Darma, Aswin Fahmi; Aseandi, Rizki; Munthe, Safaruddin (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This type of field research aims to determine the application of Khiyar rights to the practice of brick purchasing in the frame of Islamic Economic law. The method used is the descriptive method to excavate the application of Khiyar Rights in buying and selling bricks in Teluk Village, Secanggang District in North Sumatera. The research results show that buying and selling bricks is carried out by ordering (Bai As-salam) directly from the brick traders. Thus, this research finds that both Khiyar Syarat and Khiyar Aib have not properly implemented according to fiqh and the Compilations of Islamic Economic Law (Kompilasi Hukum Ekonomi Islam/KHES). This research makes a significant addition to our comprehension of the dynamics implementation of Khiyar Rights in accordance to the Compilations of Islamic Economic Law.